Digital Marketing Strategies for Enhancing Sales and Empowering MSMEs: A Sharia Economic Perspective - Okta Supriyaningsih; Diah Mukminatul Hasimi; Fernandes Tesar Bramtheo (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2025)
In the digital era, information technology has fundamentally changed the marketing patterns of SMEs. Conventional marketing has transformed into digital marketing, enabling real-time global transactions. Although SMEs play a strategic role in the national economy (absorbing labor and increasing community income), digital market penetration among SMEs remains low; for example, only around 19% of SMEs actively utilized digital marketing in 2022. This study used a descriptive qualitative approach based on a literature review. The findings indicate that digital marketing strategies that integrate Islamic economic principles (such as fairness, transparency, and halal certification) can increase sales and empower SMEs. For example, strategic actions such as improving product quality according to SNI standards, attractive packaging, utilizing marketplaces and social media, developing digital brands, and implementing halal labels have provcen effective. Furthermore, attention must be paid to Sharia ethics in online marketing to avoid practices such as ghabn (excessive mark-ups), fraud, or data security risks. The synergy between digitalization and Sharia principles can ultimately create sustainable, ethical, and highly competitive SMEs.